Estimation of calcitonin and calcitonin gene-related peptide-α in bone calcification in quail during laying period - Hadeel M. Hameed; Soulaf J. Kakel (Iraqi Journal of Veterinary Sciences)
Maintaining the balance of calcium, phosphorus, and their regulating hormones is essential in laying hens to preserve the quality of the eggs and the framework. However, the physiological regulation of these systems is quite specific. Consequently, the present study intended to estimate the level of these minerals and their regulating hormones during different egg-laying periods. Female quails were used as a model for laying hens. In this study, 60 female quails were used, divided into three age groups: the early phase (4 weeks of age), the peak phase (8 weeks of age) and the late phase (12 weeks of age), with 20 birds per group. The outcomes of the study indicate an elevation in the level of calcium and calcitonin during the peak and final period of egg production, followed by a rise in the quantity of gene-related peptide-α during the final period of egg laying, with a strong positive relationship between the level of phosphorus and calcium, as well as between gene-related peptide-α and calcitonin during the peak and final period of egg production. We conclude from this study that the level of calcium and the hormones regulating it are affected by the bird's age, in addition to a strong correlation between the level of minerals measured in this study and these hormones and the age of the bird and its productive status.